Attention, learning disability subtypes, and the naming of pictures and words. - Greenham, Stephanie Lynn. (University of Ottawa (Canada), 1999)
A series of three studies was conducted to examine the effects of attention and semantic relation on the processing of pictures and words in adults, normally achieving children, and children with specific learning disabilities (LD) in reading and spelling versus arithmetic. Event-related potentials (ERPs) were recorded during a naming task for pictures and words presented individually and in superimposed picture-word pairs in which the meanings of the pictures and words were either congruent, semantically associated, or incongruent. Participants were required to direct their attention to either pictures or words in the superimposed conditions by naming the task-relevant stimulus. Physically, the superimposed picture-word pairs were the same in each condition. A negative ERP wave occurring approximately 450 ms post-stimulus (N450) was of particular interest in this work, as this wave is sensitive to linguistic and semantic processing and has been useful in differentiating LD subtypes. For adults and normally achieving children, distinct ERP waveforms were observed for individually presented pictures and words. Although there were developmental differences in the ERPs to pictures, distinct waveforms were maintained for pictures and words presented in the superimposed pairs for both groups. This finding affirms the independent attentional processing of pictures and words. Whereas, for adults, there was evidence for automatic and controlled processing of words and pictures, respectively, there was little evidence that children processed the words automatically to the same degree. Children were also less efficient than adults at managing attentional resources. Children with two subtypes of LD based on reading and spelling (RS) or arithmetic (A) achievement were differentiated from one another and from normally achieving controls on the picture-word naming task. Compared to controls, Group RS displayed naming deficits for pictures and words and smaller N450 waves to words. Their N450 to pictures was normal. These effects were indicative of deficient linguistic processing but intact visual-spatial processing. Group A displayed a specific picture-naming deficit and smaller N450 waves to words and pictures. When attending to pictures in the superimposed pairs, Group A failed to develop an early negative wave thought to reflect processes involved in the discrimination of task-relevant stimuli. This effect may indicate early deficiencies in visual-spatial processing, possibly at the stage of object identification. Overall, these effects provide support for a typology of LD based upon patterns of academic achievement and neurocognitive performance (Rourke, 1982, 1989).
Keywords: Psychology, Developmental.